Rectal Gastrointestinal Stromal Tumor Poor Response to Imatinib: A Case Report - Majid Einakchi; Alireza Samimi; Tooraj Zandbaf; Narges Mesbah (Clinical Case Reports, 2026)
ABSTRACT A 63‐year‐old man presented with persistent constipation lasting 6.5 months. Digital rectal examination revealed a soft‐tissue lesion near the anal verge without bleeding. Further evaluation identified a rectal mass. Treatment with imatinib for 6 months showed no significant response. The patient subsequently underwent surgical resection, with favorable short‐term clinical outcomes.